(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Effective credit portfolio management is a cornerstone of financial stability and profitability for commercial banks. In the dynamic landscape of modern finance, managing credit risk is increasingly complex, requiring robust strategies to mitigate potential losses and optimize returns. The primary goal is to ensure that the credit portfolio aligns with the bank’s risk appetite and regulatory requirements while supporting sustainable growth.